The Effectiveness of Android Teaching Materials Based on Local Wisdom in Improving Students’ Writing Skill - Intan Sari Ramdhani; Asep Muhyidin; Sholeh Hidayat (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research aims to investigate the effectiveness of Android teaching materials based on local wisdom in improving student's writing skills in Indonesian language learning subjects at the junior high school level. Method: This research used a quantitative approach with the type of quasi-experimental research. The sample of this research was two classes (control and experiment class) from VII students of Junior High School 7 Tangerang City, which consists of 60 students. Results: The pretest and post-test results indicated a significantly different effect on students' writing skills between the control and experimental classes after being given Android teaching materials based on Local Wisdom in Indonesian language learning at the Junior High School level. Novelty: This research used new, unique elements of android teaching materials integrated with Tangerang local wisdom to help students acquire the materials more exciting and beneficial, especially in Indonesian language learning.